Caring for Patients from Different Cultures - Galanti, Geri-Ann (Book collections on Project MUSE., 2008)
Today's health care professional serves a multicultural population and must understand how cultural misunderstandings can result in inferior medical care and health care disparities. The fourth edition of this classic work provides over 250 case studies illustrating what can go wrong, as well as what culturally competent clinicians can do right.